1993
DOI: 10.1016/s0006-3495(93)81165-2
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric-like kinetic cooperativity of the bacteriorhodopsin molecules in purple membranes

Abstract: The kinetics of the absorption changes accompanying the photocycle of bacteriorhodopsin (BR) strongly depend on the intensity of the exciting short laser pulse. The decrease in the flash intensity dependence of the M kinetics after different extents of bleaching of the purple membranes by hydroxylamine proves the existence of a cooperative interaction between the photocycling BR molecules. The yield of the slow component of the M decay (M(s)) is a quadratic function of the extent of the fraction cycling. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
0
29
2
Order By: Relevance
“…We concluded that this altered decay kinetics is caused by the interaction between bR molecules that are excited together not within a trimer but within a 'trefoil'. Earlier works have also reported that the spectroscopically measured kinetics of the bR photocycle is altered depending on light intensity, and attributed the observed cooperative effects to neighboring effects within trimers (Rehorek et al, 1979;Tokaji, 1993) or general crowding effects in the lattice (e.g., Varo et al, 1996). However, the cooperative effects observed in these ensemble-averaged spectroscopic measurements are not as distinct as those observed by HS-AFM, which is due likely to the bipolar nature of the cooperativity.…”
Section: Analysis Of Reaction Kinetics and Its Comparison Between D96mentioning
confidence: 95%
“…We concluded that this altered decay kinetics is caused by the interaction between bR molecules that are excited together not within a trimer but within a 'trefoil'. Earlier works have also reported that the spectroscopically measured kinetics of the bR photocycle is altered depending on light intensity, and attributed the observed cooperative effects to neighboring effects within trimers (Rehorek et al, 1979;Tokaji, 1993) or general crowding effects in the lattice (e.g., Varo et al, 1996). However, the cooperative effects observed in these ensemble-averaged spectroscopic measurements are not as distinct as those observed by HS-AFM, which is due likely to the bipolar nature of the cooperativity.…”
Section: Analysis Of Reaction Kinetics and Its Comparison Between D96mentioning
confidence: 95%
“…The effect of actinic light has either been ignored (e.g. Lanyi et al, 1992), explained by invocation of photocooperativity (Ohno et al, 1981;Dancshazy et al, 1988;Tokaji, 1993), or by heterogeneity of BR populations (e.g. Hendler et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that it is possible to explain the data purely on cooperativity, but does not establish that this is the case. We also examined direct evidence which was interpreted as a strong experimental case for cooperativity (Tokaji andDancshazy, 1991, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently rediscovered effect, the actinic light density dependence of the photocycle kinetics [2] and the origin of it, a photocooperativity among the neighboring BR molecules in the purple membrane [3], will probably affect the solution of this latter problem: in the case of a sample containing the mixture of the photocycling molecules with and without photocycling neighbors, the appearance of at least two parallel pathways seems to be natural. One pathway corresponds to the unaltered photocycle and the other to the altered one.…”
Section: Introductionmentioning
confidence: 99%